CREB1 spatio-temporal dynamics within the rat pineal gland - Farías Altamirano, Luz Estefanía (2023)
In the rat pineal gland (PG), cyclic AMP responsive element-binding protein 1 (CREB1) participates in the nocturnal melatonin synthesis that rhythmically modulates physiology and behavior. Phosphorylation of CREB1 is one of the key regulatory steps that drives pineal transcription. The spatio-temporal dynamics of CREB1 itself in the different PG cell types have not yet been documented. In this study we analyzed total CREB1 in the rat PG via Western blot and fluorescence immunohistochemistry followed by confocal laser-scanning microscopy and quantitative analysis. Total CREB1 levels remained constant in the PG throughout the light:dark cycle. The distribution pattern of nuclear CREB1 did vary among PG cell types. Pinealocytes emerged to have discrete CREB1 domains within their nucleoplasm that were especially distinct. The number, size, and location of CREB1 foci fluctuated among pinealocytes, within the same PG and among Zeitgeber times (ZTs). A significantly larger dispersion of CREB1-immunoreactive nuclear sites was found at night. However, the overall transcription activity was mostly conserved between the light and dark phases, as shown by the expression of a particular phosphorylated form of the RNA polymerase II (RNAPII-pSer5CTD). Suppression of the nocturnal norepinephrine pulse by chronic bilateral superior cervical ganglionectomy increased CREB1 dispersion in pinealocyte nuclei at early night, as compared to sham-derived cells. In addition, differences in CREB1 distribution were found between sham-operated and non-operated rats at ZT14. Together, these data suggest that in mature pinealocytes nuclear CREB1 is subjected to a dynamic spatio-temporal distribution. Further studies are necessary to elucidate the underlying mechanisms and to understand the impact of CREB1 reorganization in the pineal transcriptome.